Women surviving the stigma resulting from aids - Carvalho, Carolina Maria de Lima (Rev Rene, 2008)
It has been more than two decades that the world has lived with the HIV. Within the passing years we’ve learned a lot about ways of transmission, more efficient medical treatments, more accurate laboratory results, immunity, and so on. It’s still evident, however, the stigma experienced with the discovery of the disease. That signalizes that the person is stamped and rejected. To carry a stigma means to carry a characteristic not accepted by the society. Based on this fact, those people have gone through many embarrassing situations and their chances of living a normal life have been reduced.